Kepatuhan konsumsi tablet Fe, tingkat kecukupan konsumsi Fe dan vitamin B12 berkaitan dengan anemia pada ibu hamil - Norhasanah Husaini; Nor Arpianti Eka Wardani (ARGIPA (Arsip Gizi dan Pangan), 2021)
Anemia is a common nutritional problem in pregnant women, which can have an impact on morbidity and mortality in pregnant women and fetuses. Anemia is closely related with intake of nutrients such as iron and vitamin B12 which are essential for the formation of blood hemoglobin (Hb) for the oxygen supply from blood cells to tissues. The purpose of this study is to analyze the relationship of iron supplementation, adequacy of Fe consumption and vitamin B12 with anemia based on Hb levels. The research method uses cross sectional design for pregnant women as many as 80 people. The collection of compliance data in consuming iron was carried out using questionnaires, intake data was collected by food frequency method, while anemia data was collected by looking at secondary data. Analysis of relationships between variables using pearson chi square statistical test. The results showed significant relationship between compliance in consuming Fe tablets, adequacy levels of Fe and vitamin B12 with anemia (p<0.05). There is a need for motivation in fulfilling the nutritional adequacy of pregnant women, because the role of nutrition during pregnancy is so important, so that a good pregnancy, and optimal health for both mother and fetus can be realized.